Placemaking for the regeneration of the Costanzo Ciano neighbourhood in Piacenza - Daniele Fanzini; Gianpiero Venturini; Irina Rotaru; Carlo Parrinello; Angelo De Cocinis (Techne, 2020)
This article provides insights on the urban regeneration project conduced in the densely populated centre of the “Costanzo Ciano” neighbourhood of Piacenza. Financed by MIBAC - Ministry of Heritage and Culture through the Creative Living Lab programme, the project is configured as a participatory urban regeneration action (Placemaking) aimed at testing various possible solutions for a more structured future renewal intervention. The organisational formula adopted distinguishes through the active involvement of the inhabitants at both the design and realisation stages. The output consists in the product to which the inhabitants have contributed but also, and most importantly, in the social relationships which have been formed, through which, the functional plan for the future renewal intervention has been laid out. The experience coherently follows the URBACT method principles while its cultural and practical implications refer to both the “dilemmas” theme1 posed by the current European debate regarding the strategic development of public spaces and the Placemaking tool in the Living Labs 2.0 formula2, for an innovative governance straddling theory and practice.